2017
DOI: 10.1155/2017/3194738
|View full text |Cite
|
Sign up to set email alerts
|

A Severe Case of Lymphomatoid Papulosis Type E Successfully Treated with Interferon-Alfa 2a

Abstract: Lymphomatoid papulosis (LyP) is a benign papulonodular skin eruption with histologic features of malignant lymphoma. A new variant of LyP which was termed “type E” was recently described with similar clinical and histological features to angiocentric and angiodestructive T-cell lymphoma. LyP type E is characterized with recurrent papulonodular lesions which rapidly turn into hemorrhagic necrotic ulcers and spontaneous regression by leaving a scar. None of the available treatment modalities affects the natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…To our knowledge, our case shows the longest course of LyP type E reported to date 2, 6. The disease course is benign and indolent despite its aggressive, malignant appearance on histology, which highlights the importance of clinicopathologic correlation for diagnosis of angiodestructive LyP.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…To our knowledge, our case shows the longest course of LyP type E reported to date 2, 6. The disease course is benign and indolent despite its aggressive, malignant appearance on histology, which highlights the importance of clinicopathologic correlation for diagnosis of angiodestructive LyP.…”
Section: Discussionmentioning
confidence: 58%
“…Bexarotene and topical mechlorethamine, both of which are approved by the US Food and Drug Administration for mycosis fungoides/Sézary syndrome, can also be used in cases of extensive LyP 10 . Case studies have also shown successful management of LyP using interferon alfa-2a 2 . For cases refractory to methotrexate, national guidelines suggest low-dose brentuximab vedotin 10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its histology and immunophenotypes were consistent with LyP, and were clearly different from the later lymphoma. A severe clinical course, in terms of a large tumor size and an increased number of ulcerative lesions sized more than 2 cm, has been reported in LyP type E 10,11 . Although angiodestruction was not apparent in the present case, other types of LyP may also present with severe clinical characteristics; this aspect is important to consider to prevent overdiagnosis.…”
Section: Discussionmentioning
confidence: 49%
“…14 LyP E is an even rarer subtype, with 22 cases having been described since its first description in 2013. 7,[20][21][22][23][24] The reported cases show a male predominance, with an age range of 8-77 years. 7,[20][21][22][23][24] In our series, we confirm the previously described clinical aspects of the lesions, i.e.…”
Section: Discussionmentioning
confidence: 99%